2010
DOI: 10.4269/ajtmh.2010.09-0218
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Risk Factors for the Incidence of American Cutaneous Leishmaniasis in a Sub-Andean Zone of Colombia (Chaparral, Tolima)

Abstract: Environmental risk factors for cutaneous leishmaniasis were investigated for the largest outbreak recorded in Colombia. The outbreak began in 2003 in Chaparral, and in the following five years produced 2,313 cases in a population of 56,228. Candidate predictor variables were land use, elevation, and climatic variables such as mean temperature and precipitation. Spatial analysis showed that incidence of cutaneous leishmaniasis was higher in townships with mean temperatures in the middle of the county's range. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 27 publications
3
52
0
6
Order By: Relevance
“…Esse resultado mostra o caráter ocupacional da doença nesses territórios, a relação em que o ambiente silvestre alterado pelas práticas agrícolas em áreas rurais pode determinar a ocorrência de casos. Nossos resultados são consistentes com os encontrados em trabalhos anteriores, que também identificaram o ambiente rural 8,12 e áreas de floresta favoráveis para focos de LTA 7,8,20,21 .…”
Section: Figuraunclassified
See 1 more Smart Citation
“…Esse resultado mostra o caráter ocupacional da doença nesses territórios, a relação em que o ambiente silvestre alterado pelas práticas agrícolas em áreas rurais pode determinar a ocorrência de casos. Nossos resultados são consistentes com os encontrados em trabalhos anteriores, que também identificaram o ambiente rural 8,12 e áreas de floresta favoráveis para focos de LTA 7,8,20,21 .…”
Section: Figuraunclassified
“…As nossas obeservações corroboram o estudo realizado em Tolima, na Colômbia, onde a presença de floresta ou arbusto apresentou um risco de transmissão de LTA de 2,6% (IC95%: 0,5-4,9%) para cada percentual a mais de cobertura vegetal 21 .…”
Section: Figuraunclassified
“…The transmission of visceral leishmaniasis and the proliferation of the vector are affected by multiple factors that determine the risk of contracting the disease, such as temperature, forestation, social conditions, organic matter accumulation, and population displacement 16,17 . Other studies have shown that rainfall and temperature infl uence (in a variable way) the population of phlebotomines, an important link in the transmission of VL, depending on the region where the research was carried out 18,19 .…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…The co-existence and interaction of the parasite, the vector and the host are affected by changes in both biotic and abiotic setups [44]. Human population pressure is a main reason to bring changes in these setups [45,46]. This human activity is also reason for change in climate, which in-turn influences the transmission of leishmaniasis in an area.…”
Section: Human Activity and Leishmania Transmissionmentioning
confidence: 99%